ANALYZING OF PRODUCT AS A SERVICE METHOD IN CONTROLLING PRODUCTION COST BASED ON COMPANIES IN UNITED KINGDOM - Muhammad Farraz Octoberry; Pascal Wittendorp (Diponegoro Journal of Accounting, 2023)
This thesis explains most of the concepts of Product as a Service (PaaS), which is a potential change in buying and selling patterns of goods to consumers and producers. In this case, explaining the consumer as a point involved in the ownership-based model, buying products directly with the responsibility for maintenance. The Product as a service method aims to offer products through a service-oriented model, where consumers pay for the results obtained from the product rather than owning it directly. This thesis examines aspects of Product as a service by explaining some of the basic principles and business models as well as their potential for the financial stability of a company as a producer. By analyzing companies that use the Product as a Service method, the author aims to analyze whether this method can impact their production costs in order to get a stable financial level. With this, it is necessary to review the comprehensive literature and analyze a company's annual report. The findings of this thesis will contribute to existing knowledge by providing an understanding and the impact that will occur if a company implements the Product as a Service concept as their business strategy. In the end, Product as a service has the potential to make the company's financial stability and policies for customer satisfaction, and it can be implemented in other companies in various countries in a more sustainable future.